TINJAUAN GEOGRAFIS DAN STRATEGI PENGEMBANGAN DESA WISATA COKRO KECAMATAN TULUNG KABUPATEN KLATEN - Maharani, Najwa Putri (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2025)
This research aims to identify geographical factors, assess the level of feasibility, and analyze development strategies for Cokro Tourism Village. This research used a quantitative approach with a survey method. The data used consisted of primary data obtained through field observations and interviews, and secondary data sourced from institutions, journals, books and village profiles. The analysis techniques used included geographical analysis, analysis of the Supportability of Tourism Objects and Attractions (ADO-ODTWA) using the scoring method, descriptive percentage analysis, and IFE, EFE, and SWOT matrix analysis. The results showed that influential geographical factors include landform, rock, air temperature, and slope. Based on the ADO-ODTWA assessment, attractions, infrastructure, and activities are classified as very potential, accessibility is classified as potential, while accommodation is classified as less potential. The descriptive analysis assessment also shows that attractions and activities are in the high potential category, while accessibility, accommodation, and infrastructure are in the potential category. Based on SWOT analysis, Cokro Tourism Village is in quadrant I with an X value of 0.83 and Y value of 1.62, which indicates a progressive strategy.